Rheological properties and coalescence stability of degassed crude oil emulsion: Influence of supercritical CO2 treatment - Guangyu Sun; Fujun Sheng; Qingyi Li; Chuanxian Li; Fei Yang; Bo Yao; Yansong Zhao (Journal of CO2 Utilization)
With the technology of enhanced oil recovery by supercritical CO2 flooding (scCO2-EOR) popularized and applied, the water-in-oil (W/O) emulsion can be easily formed in the surface gathering pipeline when the produced crude oil and water flows through the pump and throttle valve. The formation of emulsion increases the resistance and cost of pipeline transportation tremendously. Considering the detrimental effect of emulsion formation, we focus on the effect of CO2 treatment on rheological properties and stability of emulsion within the pipeline. It is hoped to provide some guidance for the increase in the efficiency of pipeline transportation and emulsion treatment. In this work, a device was developed to simulate the scCO2 treatment conditions in the reservoir. The variations in gelation process, pour point, yield stress, viscosity-temperature property and coalescence stability of emulsion were studied experimentally under treatment conditions (without any treatment, treated by 80 ℃, 5 MPa, treated by 80 ℃, 15 MPa, treated by 80 ℃, 25 MPa). The effect of scCO2 treatment on gelation property of emulsion was reported for the first time. The results show that the storage modulus and gelation temperature are increased obviously after the scCO2 treatment, which is owing to the influence of scCO2 treatment on wax crystals morphology and gelation structure of system. As for the pour point, yield stress, and viscosity/apparent viscosity, they are all enlarged greatly after scCO2 treatment, due to the scCO2 extraction effect. Finally, the sizes of emulsion droplets gradually decrease with the treatment pressure, leading to the improvement of emulsion stability.